An ESIPT‐Based Ratiometric Fluorescent Probe for Highly Sensitive and Rapid Detection of Sulfite in Living Cells. Issue 10 (7th October 2019) - Liu, Yupeng; Ren, Tian‐Bing; Cheng, Dan; Hou, Jianing; Su, Dongdong; Yuan, Lin
Abstract: The novel ratiometric fluorescent probe HPQRB with an ESIPT effect based on Michael addition for highly sensitive and fast detection of sulfite in living HepG2 cells is reported. HPQRB can be easily synthesized by a two‐step condensation reaction. HPQRB has a large emission shift (Δ λ =116 nm), which is beneficial for fluorescence imaging research, and its sulfite‐responsive site is based on a rhodamine‐like structure with the emission peak at 566 nm, which decreases with increasing sulfite concentration. and its HPQ structure always has an ESIPT effect throughout the reaction process, keeping the emission peak at 450 nm as a self‐reference. In particular, HPQRB has high selectivity for sulfite and responds quickly (within 30 s) with a low detection limit (44 nM). Furthermore, HPQRB has been successfully used for fluorescence imaging of sulfite in HepG2 cells, demonstrating the superior ability to detect sulfite under physiological conditions. Abstract : Waiting for the sulfite to shine : HPQRB is a ratiometric fluorescent probe that responds quickly (within 30 s) and selectively to sulfite with a low detection limit (44 nM) and it has been successfully used for fluorescence imaging of sulfite in HepG2 cells, demonstrating the superior ability to detect sulfite under physiological conditions.